Differences in health behavior and nutrient intake status between diabetes-aware and unaware Korean adults based on the Korea national health and nutrition examination survey 2016–18 data: A cross-sectional study - Sharma, Anshul; Lulu, Chen; Song, Kee-Ho; Lee, Hae-Jeung (Frontiers in Public Health, 2022)
Background: The aim of this study was to investigate the nutritional intakes and treatment regimens of Korean patients with type 2 diabetes who were aware of their condition. Methods: Participants (n = 16582) aged ≥ 19 years from the 2016-18 National Health and Nutrition Survey were divided into diabetes-aware and unaware groups and the variables were compared. Results: Among 1,906 (11.5%) diabetic adults, 1,433 (75.2%) were aware of their condition; 130 (9.1%) had nutrition education, and 1,340 (93.5%) were in the diabetes-aware treatment group. The diabetes-aware group had higher average age (P < 0.0001) and lower average BMI (P = 0.0015) than the unaware group. Intake of total fat (P = 0.0034), saturated fatty acids (P = 0.0021), riboflavin (P = 0.0035) and niacin (P = 0.0228) was significantly higher in the unaware group than in the diabetes-aware group, after adjusting energy intake for age and sex. Current smoking (P = 0.0046) and heavy drinking (P < 0.0001) rates were higher in the unaware group, whereas fiber intake (P = 0.0054) was lower in the unaware group. Higher levels of glycated hemoglobin were found in the group treated for diabetes (7.2%) than in the no-treatment (6.8%) group (P = 0.0048). Diabetes control was significantly better in the high income group. Conclusions: There is a need to strengthen nutritional education to prevent diabetes and improve the health status of diabetic patients in Korea.